Baseline Pulse Pressure, Acute Kidney Injury, and Mortality After Noncardiac Surgery. (December 2016) - Oprea, Adriana D.; Lombard, Frederick W.; Liu, Wen-Wei; White, William D.; Karhausen, Jörn A.; Li, Yi-Ju; Miller, Timothy E.; Aronson, Solomon; Gan, Tong J.; Fontes, Manuel L.; Kertai, Miklos D.
Abstract : BACKGROUND: Increased pulse pressure (PP) is an important independent predictor of cardiovascular outcome and acute kidney injury (AKI) after cardiac surgery. The objective of this study was to determine whether elevated baseline PP is associated with postoperative AKI and 30-day mortality after noncardiac surgery. METHODS: We evaluated 9125 adult patients who underwent noncardiac surgery at Duke University Medical Center between January 2006 and December 2009. Baseline arterial blood pressure was defined as the mean of the first 5 measurements recorded by the automated record keeping system before inducing anesthesia. Multivariable logistic regression analysis was performed to determine whether baseline PP adjusted for other perioperative risk factors was independently associated with postoperative AKI and 30-day mortality. RESULTS: Of the 9125 patients, the baseline PP was <40 mm Hg in 1426 (15.6%), 40–80 mm Hg in 6926 (75.9%), and >80 mm Hg in 773 (8.5%) patients. The incidence of AKI was 19.8%, which included 8.4% (151 patients) and 4.2% (76 patients) who experienced stage II and III AKI, respectively. In the risk-adjusted model for postoperative AKI, elevated baseline PP was associated with higher odds for postoperative AKI (adjusted odds ratio [OR] for every 20 mm Hg increase in PP, 1.17; 95% confidence interval [CI], 1.10–1.25; P < .0001). Also elevated baseline preoperative PP was significantly associated with mild (stage I; OR, 1.19; 95% CI, 1.11–1.27; P < .0001), but not with more advanced stages of postoperative AKI or with an incremental risk for 30-day mortality. CONCLUSIONS: We found a significant association between elevated baseline PP and postoperative AKI in patients who underwent noncardiac surgery. However, elevated PP was not significantly associated with more advanced stages of postoperative AKI or 30-day mortality in these patients. Abstract : Supplemental Digital Content is available in the text.Published ahead of print September 7, 2016.